Association between Electronic Health Record Implementations and Hospital-Acquired Conditions in Pediatric Hospitals - Rabbani, Naveed; Pageler, Natalie M.; Hoffman, James M.; Longhurst, Chris; Sharek, Paul J. (Applied Clinical Informatics, 2023)
Background Implementing an electronic health record (EHR) is one of the most disruptive operational tasks a health system can undergo. Despite anecdotal reports of adverse events around the time of EHR implementations, there is limited corroborating research, particularly in pediatrics. We utilized data from Solutions for Patient Safety (SPS), a network of 145+ children's hospitals that share data and protocols to reduce harm in pediatric care delivery, to study the impact of EHR implementations on patient safety.Objective Determine if there is an association between the time immediately surrounding an EHR implementation and hospital-acquired conditions (HACs) rates in pediatrics.Methods A survey of information technology leaders at pediatric institutions identified EHR implementations occurring between 2012 and 2022. This list was cross-referenced with the SPS database to create an anonymized dataset of 27 sites comprising monthly HAC and care bundle compliance rates in the 7 months preceding and succeeding the transition. Six HACs were analyzed: central-line associated bloodstream infection (CLABSI), catheter-associated urinary tract infection (CAUTI), adverse drug events, surgical site infections (SSIs), pressure injuries (PIs), and falls, in addition to four associated care bundle compliance rates: CLABSI and CAUTI maintenance bundles, SSI bundle, and PI bundle. To determine if there was a statistically significant association with EHR implementation, the observation period was divided into three eras: “before” (months −7 to −3), “during” (months −2 to +2), and “after” go-live (months +3 to +7). Average monthly HAC and bundle compliance rates were calculated across eras. Paired t-tests were performed to compare rates between the eras.Results No statistically significant increase in HAC rates or decrease in bundle compliance rates was observed across the EHR implementation eras.Conclusion This multisite study detected no significant increase in HACs and no decrease in preventive care bundle compliance in the months surrounding an EHR implementation.
Keywords: quality; process improvement; electronic health records; safety; pediatrics; implementations and transitions